Selective immunoglobulin A deficiency and recurrent infections in children: how deep is this issue? - Mirela Luminița Pavelescu; Irina Dijmărescu; Alexandru Dinulescu; Alexandru Sorin Păsărică; Cristina Burtescu; Cătălina Elena Lavric; Gheorghiță Jugulete; Daniela Păcurar (Hygeia Press di Corridori Marinella, 2024)
Background: Selective immunoglobulin A deficiency (SIgAD) is the most common primary immunodeficiency. Although most patients with SIgAD do not develop symptoms, some conditions related to SIgAD have been reported, particularly recurrent respiratory tract infections and infections caused by encapsulated microorganisms. Our objective was to evaluate the association of SIgAD with other pediatric conditions and extract data to establish an individualized protocol for managing patients with SIgAD. Methods: We conducted a 3-year retrospective epidemiological study of 57 pediatric patients (aged 4-17 years) diagnosed with SIgAD after admission to the Pediatrics Department of "Grigore Alexandrescu" Emergency Children's Hospital in Bucharest, Romania. The type of infection (location, etiologic agent, and severity) and associated allergic and immune disorders were analyzed. Results: Respiratory tract infections were the main conditions observed in patients with SIgAD (86.0%), and recurrence was reported in over half of the patients (54.4%). Overall, 42.1% of patients had acute digestive involvement. Of the 93 infections (positive culture), in 37 cases (39.8%) encapsulated germs were involved. Among the encapsulated germs, Klebsiella pneumoniae was isolated in 11 cases (29.7%), Staphylococcus aureus in 9 cases (24.3%), Escherichia coli, Streptococcus pneumoniae and Haemophilus influenzae each in 5 cases (13.5%), and Pseudomonas aeruginosa was identified in 2 cases (5.4%). Several patients had recurrent or multiple infections - for 20 (35.1%) out of the 57 children, 2 microorganisms were identified at different points in time during the study period, and for 8 children (14.0%), 3 microorganisms were identified at the same time. Allergic-associated markers or allergic events were found in 20 children (35.1%) and celiac disease was diagnosed in 3 patients (5.3%). Conclusions: Although SIgAD is a primary immunodeficiency that is not immediately life-threatening, infections are potentially disabling. Therefore, primary care physicians and pediatricians should closely monitor patients with SIgAD.